2011
DOI: 10.1002/ijc.25930
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p53 and cell proliferation by resveratrol and its derivatives in breast cancer cells: An in silico and biochemical approach targeting integrin αvβ3

Abstract: Resveratrol is a grape polyphenol with cancer preventative activities in tissue culture and animal model studies. Potential of resveratrol as a broad-based chemopreventive agent have been questioned by its limited bioavailability. The bioefficacy of resveratrol was compared with its derivatives, triacetyl-resveratrol (trans-3,5,4 0 -triacetylstilbene) and trimethoxy-resveratrol (trans-3,5,4 0 -trimethoxystilbene) in both estrogen receptor-a (ERa)-positive MCF-7 and ERa-negative MDA-MB-231 breast cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 30 publications
5
44
1
Order By: Relevance
“…In an experiment treating MDA-MB231 cells with resveratrol, the downstream p53-dependent proapoptotic genes including p53, c-fos, c-jun, p21, PIG3, and BAD induced by resveratrol were also confirmed (43). Upstream of this molecular pathway was also suggested to be resveratrol's binding to integrin αvβ3, which caused subsequent activation of the ERK and/ or p38 kinase pathway to finally activate p53 (45). In gastric cancer cells like SGC7901, resveratrol induced survivin decrease could also lead to cell cycle arrest, such as G0/G1 phase up-regulation and S, G2/M phase distribution down-regulation (51).…”
Section: Apoptosis Led By Cell Cycle Arrest: Importance Of P53 and P21mentioning
confidence: 93%
“…In an experiment treating MDA-MB231 cells with resveratrol, the downstream p53-dependent proapoptotic genes including p53, c-fos, c-jun, p21, PIG3, and BAD induced by resveratrol were also confirmed (43). Upstream of this molecular pathway was also suggested to be resveratrol's binding to integrin αvβ3, which caused subsequent activation of the ERK and/ or p38 kinase pathway to finally activate p53 (45). In gastric cancer cells like SGC7901, resveratrol induced survivin decrease could also lead to cell cycle arrest, such as G0/G1 phase up-regulation and S, G2/M phase distribution down-regulation (51).…”
Section: Apoptosis Led By Cell Cycle Arrest: Importance Of P53 and P21mentioning
confidence: 93%
“…Binding to integrin avb3 and control of cell proliferation and p53 were chosen as targets for comparative analysis using an in silico and biochemical approach. 20 Resveratrol and triacetyl-resveratrol interacted avidly and specifically with integrin avb3 through binding at the site targeted by the high affinity cyclic Arg-Gly-Asp (RGD) peptide. In contrast, binding of trimethoxy-resveratrol to this site was substantially less robust.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…20 Further, stilbene-elicited signaling cascade leading to p53 activation was examined and results showed that resveratrol and triacetyl-resveratrol induced both ERK and p38 phosphorylation, whereas only marginal changes in state of phosphorylation in these two kinases were observed in trimethoxy-resveratrol-treated cells. 20 Estrogen plays a crucial role in the development of breast cancer, and the inhibition of estrogen synthesis has been an important target for the prevention and treatment. As a result of its structural resemblance to estrogen, resveratrol's agonistic and antagonistic properties on ER have been examined.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Evidence for a possible role of p53 in M phase came from observations that p53 contributes to the control of centrosome duplication and to the prevention of DNA replication is impaired by spindle inhibitors (Talos and Moll, 2010). In recent reports indicate that both estrogen receptor positive (MCF-7) and triple negative (MDA-MB-231) breast cancer cells were exposed to synthetic or natural derived anti-cancer drugs remarkable arrest cell cycle via accumulation in G2/M phase through the inhibition of Akt activity and p53-independent or p53-dependent activation of p53 inducible proteins such as p21/p53R2 /CDKN1A and GADD45A (De Santi et al, 2011;Hahm et al, 2011;Hsieh et al, 2011). It is noteworthy that A. camphorata significantly up-regulates p53 tumor suppressor gene in human colorectal carcinoma cells (Lien et al, 2009), and human prostate cancer cell lines .…”
Section: A Camphorata Up-regulates Tumour-suppressor Genesmentioning
confidence: 99%